The long road to the Industrial Revolution : the European economy in a global perspective, 1000-1800 - Zanden, J. L. van (Global economic history series ;, 2009)
A ~The Long Road to the Industrial Revolutiona (TM) offers a new explanation of the origins of the industrial revolution in Western Europe by placing development in Europe within a global perspective. It focuses on its specific institutional and demographic development since the late Middle Ages, and on the important role played by human capital formation.